Depression, anxiety and stress among patients with hematological malignancies and the association with quality of life: a cross-sectional study - Papathanasiou, Ioanna V. (Med Pharm Rep, 2020)
AIM: To evaluate psychological distress and quality of life of patients with hematological malignancies, as well as to identify the prognostic factors that aggravate their condition. METHODS: A cross-sectional, descriptive study including 87 patients with Hematological Malignancies was conducted. Data were collected with an anonymous questionnaire consisted by A) a sheet with socio-demographic characteristics, B) the Depression, Stress and Stress Scale (DASS21), and C) World Health Organization Life Quality Scale (WHOQOL - BREF30). The processing and statistical analysis of the empirical material of the research were done using the SPSS (Statistical Package for Social Science) 22.0. RESULTS: The results showed that the age of the sample averaged 71.22 years (SD = 8.71). Regarding their marital status, single mothers were 9.2%, married 62.1%. With regard to disease-related features, 28.7% of patients had Hodgkin’s Lymphoma, 27.6% Chronic Lymphocytic Leukemia, 27.6% MDL and 16.1% of patients had myelodysplastic syndrome Multiple myeloma. In the investigation of the relationship between the Mental health Scale and the Quality of Life, negative correlations of Depression, Stress, Stress and the total DAS Scale with all dimensions of Patient Quality of Life were found. CONCLUSIONS: Higher levels of psychological distress and poor mental health are associated with a low level of quality of life.